(untitled) (Texas Journal of Medical Science, 2025)
The article describes a clinical case of Behçet’s disease, a rare systemic vasculitis characterized by recurrent orogenital ulcers, ocular and skin manifestations. Detailed anamnesis, clinical examination, laboratory tests and treatment are presented